Faktor Risiko Kejadian Diabetes Melitus Tipe Dua di RS Bhayangkara Kota Kupang - Kabosu, Renata Aryndra Sukma; Adu, Apris A.; Hinga, Indriati Andolita Tedju (Timorese Journal of Public Health, 2019)
Diabetes mellitus is a disease that causes public health problems because it is one of the causes of deaththroughout the world. This study aimed to analyze the risk factors for type 2 diabetes mellitus. The type ofresearch used is a case control study, with a retrospective approach. The location of this study is in BhayangkaraHospital on Kupang city. The sample in this study was divided into two groups, namely a case sample as muchas 37 people and a control sample as much as 37 people. Research instruments use questionnaires and medicalrecords. The data obtained were analyzed using chi square statistical test. From the results of the study it wasfound that the related factors were: age (p=0,018, OR=3,544; CI= 95%), obesity (p=0.015; OR=3.826;CI=95%), hypertension (p=0.019; OR=3,423; CI=95%), consumption pattern (p=0,017; OR=3,660; CI=95%),stress (p=0,036 OR=3,033; CI=95%). It is expected the hospital provides information through counseling orleaflets about risk and danger factors of Type 2 DM to the community and for community to be able to increaseawareness for risk factors of the Type 2 DM by diligently checking for self-detection so the treatment can bedone as early as possible.